Risk factors determining the need for second-look endoscopy for peptic ulcer bleeding after endoscopic hemostasis and proton pump inhibitor infusion - Cheng, Hsiu-Chi; Wu, Chung-Tai; Chen, Wei-Ying; Yang, Er-Hsiang; Chen, Po-Jun; Sheu, Bor-Shyang (Endoscopy International Open, 2016)
Background and study aims: The need for routine second-look endoscopy in cases of peptic ulcer bleeding remains uncertain. We investigated risk factors related to the need for second-look endoscopy after endoscopic hemostasis and proton pump inhibitor (PPI) infusion. Patients and methods: We prospectively enrolled 316 patients with peptic ulcer bleeding after endoscopic hemostasis. Second-look endoscopy was scheduled after 72-hour PPI infusion (Day-3 subgroup) or one day early (Day-2 subgroup). If early rebleeding developed within 3 days, emergent second-look endoscopy was conducted. Risk factors for early rebleeding (use of E2nd score to predict the need for early second-look endoscopy) and persistent major stigmata in the Day-3 subgroup (use of R2nd score to predict the need for routine second-look endoscopy) were analyzed using univariable and multivariable regression.Results: Excluding 10 of 316 patients with early rebleeding, the rate of persistent major stigmata was lower in the Day-3 subgroup than in the Day-2 subgroup (4.8 % vs. 15.4 %, P  = 0.002). Endoscopic epinephrine-injection monotherapy and hypoalbuminemia < 3.0 g/dL were two independent risk factors for early rebleeding (P  ≤ 0.05). The Forrest Ia-Ib type and hypoalbuminemia < 3.5 g/dL were two independent risk factors for persistent major stigmata on the day-3 second-look endoscopy (P  < 0.05). The E2nd score was highly accurate for prediction of early rebleeding (AUROC 0.86; 95 % CI, 0.73~0.99), and the R2nd score could predict persistent major stigmata at second-look endoscopy (AUROC 0.84; 95 % CI, 0.69~0.99).Conclusions: For patients with peptic ulcer bleeding, E2nd and R2nd scores can indicate the need for early and routine second-look endoscopy, respectively(Trial registration identifier: NCT02197039).